Numerical Study of Thermal Performance Improvement By Novel Structures in the Building Energy Storage Systems - (:unkn) unknown (My University, 2017)
In this work, numerical studies were conducted to investigate the effectiveness of two fin-like novel structures used for heat-transfer enhancement in two building energy storage systems including thermal energy storage and battery energy storage. Firstly, thin layer ring structure was numerically investigated for thermal performance improvement in the thermal energy storage. From the results obtained in this study, the area ratio can be increased by 4% when using the thin layer ring during the same time period. The thin layer ring structure can shorten ice formation period and increase its efficiency. Further study was conducted for the factorial analysis of three parameters, including thickness, material and arrangement of thin layer ring. From the results, it shows that ice formation period can be shortened with the increase of conductivity and area of thin layer ring, while it is also dependent on thickness. Using Taguchi method, the statistic results show that material has the greatest impact on ice increased area. After that, arrangement has relatively less influence on ice increased area. However, thickness has the trifling effect on ice-increased area. The optimal combination of each factor (parameter) has been determined, and the optimal condition is A3B2C1. That is to say, for material = copper, thickness = 1mm，and arrangement = staggered, the best result of heat-transfer enhancement was obtained among all the cases studied. The reproducibility of these conditions has been verified by two analytical results. Secondly, in battery energy storage, numerical simulations have been conducted to explore the air flow and heat transfer at different discharging rates in a horizontal rectangular channel with two different configurations of vortex generator (VG), such as rectangular rib and delta winglet. The simulation in air flow domain with characteristics of heat transfer and flow structure show that both types of vortex generators can enhance heat transfer before VGs, but only delta winglet VG can still enhance local heat transfer after it due to more vortices generated that can mix cold and hot air flow between the top and bottom thermal layers completely. The encouraging result shows that the maximum temperature of pouch cell can be decreased more by delta winglet than by rectangular rib. For the discharging rate at 5C, it can be decreased by 10% and the local Nusselt number can be increased by 38% compared to the baseline scenario without any VGs.
Keywords: Battery Energy Storage; Heat Transfer; Ice Thermal Energy Storage; Taguchi Method; Thin Layer Ring; Vortex Generator